Efektivitas Tanaman Herbal terhadap Pengobatan Diabetes Melitus - Rifa Nur Alia; Mally Ghinan Sholih (Poltekkes Kemenkes Padang, 2024)
Diabetes mellitus is a chronic metabolic condition characterized by high levels of glucose in the blood caused by a lack of insulin production by the pancreas. Herbal plant treatment can be used to treat diabetes mellitus which has the potential to help lower blood sugar levels, especially herbal plants which contain compounds without causing side effects. This research aims to conduct a comprehensive review of various plant species that have potential as alternative treatments for diabetes mellitus. The method used involves the stages of reading, understanding, comparing, summarizing, and concluding from journal literature obtained as many as 20 articles from PubMed, Google Scholar, and Elsevier sources. The results of the literature study show that from various journals studied, plant types such as starfruit leaves, cherry mistletoe, black soybean seed coats, Moringa leaves, banua nest leaves, turmeric rhizomes, Bersama abyssinica, Falcaria vulgaris, Iranian ethnobotanical herbs, Hortus Medicus herbal medicine, Allium saralicum, Huangqi (Radix Astragali) and Huanglian (Rhizoma Coptidis), cinnamon, lemongrass, bitter melon, bay leaves, and ciplukan have been proven to reduce glucose in the blood, inhibit the activity of the α-glucosidase enzyme, prevent hyperglycemia, and control the lipid profile. Based on this research, it can be concluded that the active components found in these plants have been proven to have a positive effect in antidiabetic treatment. We also encourage further research into the side effects, drug interactions, and long-term effectiveness of using herbal plants as antidiabetic therapy.